New programmes introduced to mould students with futuristic mindset - UMP, PNC
Last year was a monumental year for Universiti Malaysia Pahang (UMP) in its efforts to establish various new programmes to develop and mould graduates with a new and futuristic mindset, coupled with high standard of ethics and integrity, and equipped to explore new boundaries to compete at the international level upon graduation.